2019
DOI: 10.4093/dmj.2018.0111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Longitudinal Changes in Metabolic Syndrome Status over 2 Years on 10-Year Incident Diabetes Mellitus

Abstract: Background Metabolic syndrome (MetS) is a known predictor of diabetes mellitus (DM), but whether longitudinal changes in MetS status modify the risk for DM remains unclear. We investigated whether changes in MetS status over 2 years modify the 10-year risk of incident DM. Methods We analyzed data from 7,317 participants aged 40 to 70 years without DM at baseline, who took part in 2001 to 2011 Korean Genome Epidemiology Study. Subjects were categorized into four groups b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…In our study, among those who had been ever diagnosed with MetS during the study period, only one-fifth exhibited persistent MetS over the 4 years. This finding supports the notion of dynamic change in MetS over time, as demonstrated in previous studies [14,16,24]. From this perspective, it is important to assess the effects of the accumulation of metabolic risk factors on CVD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, among those who had been ever diagnosed with MetS during the study period, only one-fifth exhibited persistent MetS over the 4 years. This finding supports the notion of dynamic change in MetS over time, as demonstrated in previous studies [14,16,24]. From this perspective, it is important to assess the effects of the accumulation of metabolic risk factors on CVD.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have been observed for other metabolic or vascular diseases. For example, previous studies have reported that changes in MetS status over 2 years are closely associated with the development of diabetes mellitus or chronic kidney disease after 10 years [16,24]. Taken together, these findings suggest that, given the dynamic nature of MetS, a single assessment of MetS may not be sufficient for evaluating its clinical impact.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, with regard to the risk of HF, Voulgari et al [14] reported that MHO is associated with a lower risk of HF than is MUNO. However, these obesity subphenotypes defined by the status of metabolic health and obesity change dynamically over time [10,[15][16][17][18][19]. Soriguer et al [18] reported that 41.9% of MHO individuals became metabolically unhealthy during the 6-year follow-up, suggesting that obesity sub-phenotypes should account for the passage of time.…”
mentioning
confidence: 99%
“…In the article entitled “Impact of longitudinal changes in metabolic syndrome status over 2 years on 10-year incident diabetes mellitus,” Huh et al [3] examined whether changes in MetS status over 2 years can modify future risk of diabetes using a prospective cohort of 7,317 participants. They were divided into four groups, two without changes (non-MetS, persistent MetS) and two with changes (resolved MetS, incident MetS).…”
mentioning
confidence: 99%